The Drosophila homolog of vertebrate Islet1 is a key component in early cardiogenesis. - Mann, T.; Bodmer, R.; Pandur, P. (Development, 2009)
In mouse, the LIM-homeodomain transcription factor Islet1 (Isl1) has been shown to demarcate a separate cardiac cell population that is essential for the formation of the right ventricle and the outflow tract of the heart. Whether Isl1 plays a crucial role in the early regulatory network of transcription factors that establishes a cardiac fate in mesodermal cells has not been fully resolved. We have analyzed the role of the Drosophila homolog of Isl1, tailup (tup), in cardiac specification and formation of the dorsal vessel. The early expression of Tup in the cardiac mesoderm suggests that Tup functions in cardiac specification. Indeed, tup mutants are characterized by a reduction of the essential early cardiac transcription factors Tin, Pnr and Dorsocross1-3 (Doc). Conversely, Tup expression depends on each of these cardiac factors, as well as on the early inductive signals Dpp and Wg. Genetic interactions show that tup cooperates with tin, pnr and Doc in heart cell specification. Germ layer-specific loss-of-function and rescue experiments reveal that Tup also functions in the ectoderm to regulate cardiogenesis and implicate the involvement of different LIM-domain-interacting proteins in the mesoderm and ectoderm. Gain-of-function analyses for tup and pnr suggest that a proper balance of these factors is also required for the specification of Eve-expressing pericardial cells. Since tup is required for proper cardiogenesis in an invertebrate organism, we believe it is appropriate to include tup/Isl1 in the core set of ancestral cardiac transcription factors that govern a cardiac fate.